KEDISIPLINAN PENGGUNAAN APD, KEBIASAAN MEROKOK DAN PENGARUHNYA DENGAN GANGGUAN PERNAPASAN PADA POLANTAS - Nina Fentiana; Resi Reka Putri (Jurnal Kesehatan, 2018)
Vulnerable respiratory tract disorders are experienced by the Traffic Police because of exposure to pollutant substances originating from the exhaust gases of motorized vehicles that pass and dust particles in the surrounding environment. In 2013, the ILO (International Labor Organization) estimated that 2.02 million died from various diseases related to work exposed to exposure to gas, steam and dust. This study aims to determine the discipline of the use of mask and its effect on respiratory tract disorders in the Traffic Police in the Satlantas city of Medan in 2018. The type of research used is quantitative with a cross sectional approach. The number of samples analyzed by 124 people and sampling using accidental sampling technique. Data analysis using chi-square test (α = <0.05). The results of the chi-square test (α = <0.05) indicate age (p-value = 0.001), work period (p-value = 0.022), smoking habits (p-value = 0.005), discipline of the use of PPE (p-value = 0.001) has a significant relationship with respiratory problems in the traffic police. About 79.3% of the traffic police who were not disciplined using mask were known to experience respiratory complaints. From the results of the analysis it was also obtained that OR = 0.216 means that the Traffic Police that are not disciplined using mask have a chance of 0.216 times to experience respiratory problems. Efforts are needed to improve the discipline of traffic police in the use of mask when working in the field with the method of reward and punishment.ABSTRAKGangguan saluran pernapasan rentan dialami oleh Polantas (Polisi Lalu Lintas) karena paparan zat-zat polutan yang berasal dari gas buangan kendaraan bermotor yang lewat dan partikel-partikel debu yang ada di lingkungan sekitar. ILO (Internasional Labour Organization) pada tahun 2013 memperkirakan 2,02 juta meninggal dari berbagai penyakit yang berhubungan dengan pekerjaan yang terkena paparan gas, uap dan debu. Penelitian ini bertujuan untuk mengetahui kedisplinan penggunaan APD dan pengaruhnya dengan gangguan saluran pernapasan pada Polantas di Satlantas kota Medan tahun 2018. Jenis penelitian yang digunakan adalah kuantitatif dengan pendekatan cross sectional. Jumlah sampel yang dianalisis 124 orang dan pengambilan sampel menggunakan tehnik accidental sampling. Analisis data menggunakan uji chi-square (α = < 0,05). Hasil uji chi-square (α = < 0,05) menunjukkan umur (p-value=0,001), masa kerja (p-value=0,022), kebiasaan merokok (p-value=0,005), kedisiplinan penggunaan APD (p-value=0,001) memiliki hubungan yang signifikans dengan gangguan saluran pernapasan pada Polantas. Sekitar 79,3% Polantas yang tidak disiplin menggunakan APD diketahui mengalami keluhan pernapasan. Dari hasil analisis diperoleh pula OR=0,216 artinya Polantas yang tidak disiplin menggunakan APD mempunyai peluang 0,216 kali untuk mengalami gangguan pernapasan. Dibutuhkan upaya peningkatan disiplin Polantas dalam pengunaan APD pada saat bekerja dilapangan dengan metode reward dan punishment.